Larval Ecology of Gobiid Fishes in a Subtropical Embayment: Environmental Preferences and Spatiotemporal Habitat Partitioning - Zhang, Hui; Yuan, Xingwei; Ling, Jianzhong; Jiang, Yazhou (Frontiers in Marine Science, 2022)
Larval ecology of gobiid fishes in Xiangshan Bay of the east coast of China was examined from ichthyoplanktonic data collected during 10 weekly cruises in spring–early summer of 2015. Particular attention was given to their environmental preferences and spatiotemporal habitat partitioning. A total of 87, 007 gobiid larval individuals, distributed in 9 species, were collected. The thermal and salinity preferences of 6 of the 9 gobiid larvae have been determined using a quotient-rule analysis. This work filled some gaps in larval ecology of these poorly studied gobiids. Temporal succession in gobiid larvae composition was strongly evident. The bay ecosystem was mainly occupied by Asian freshwater goby Acanthogobius ommaturus, branded goby Chaeturichthys stigmatias and tank goby Glossogobius giuris, with preferences for temperature bellow 19°C during April to early May, while striped sand goby Amoya pflaumi and burrowing goby Trypauchen vagina, which preferred water temperature above 22°C, predominated the larval assemblage in early June. With respect to spatial distribution, relatively little variation was detected among species. Most of gobiid larvae exhibited little obvious habitat preference except pinkgray goby Amblychaeturichthys hexanema and A. ommaturus, which distributed preferably in the inner zone and mouth of the bay ecosystem, respectively. Water temperature was the major structuring factor of gobiid larvae assemblage structure in the bay. The gobiid larvae exhibited to be particularly susceptible to the rapid rising temperature shocks. Sharp decline in the total abundance of gobiid larvae was detected with each rapid heating process. In addition, significant shift in larval fish composition occurred following the process. The results suggest that pattern of temperature increase in spring and early summer plays a vital role in recruitment success of the gobiid larvae.